2019
DOI: 10.1111/jcmm.14880
|View full text |Cite
|
Sign up to set email alerts
|

Association of suboptimal health status with intestinal microbiota in Chinese youths

Abstract: Suboptimal health status (SHS) is a physical state between health and disease and is characterized by the symptoms of health complaints, general weakness and low energy within a period of 3 months. 1 A comprehensive Suboptimal Health Status Questionnaire-25 (SHSQ-25) was used to assess SHS, with the SHSQ-25 accounting for the multidimensionality of SHS by assessing the following: (a) fatigue, (b) the cardiovascular system, (c) the digestive tract, (d) the immune system and (e) mental status. 2 To date, the SHS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 68 publications
(166 reference statements)
1
14
0
Order By: Relevance
“…The SHSQ-25 includes 25 items constituting ve dimensions: the immune system, the cardiovascular system, the respiratory system, fatigue, and mental status [9], and it has been used in Caucasians [10], Africans [4,11], and Asian [6,12]. To screen objectively diagnostic biomarkers for SHS, several biomarkers, including cortisol [13], relative telomere length [14], intestinal microbiota [15], and metabolites [16], have been investigated. Although previous studies have indicated that multi-omics biomarkers have the potential to diagnose SHS individuals, the underlying mechanisms of SHS remain partially understood.…”
Section: Introductionmentioning
confidence: 99%
“…The SHSQ-25 includes 25 items constituting ve dimensions: the immune system, the cardiovascular system, the respiratory system, fatigue, and mental status [9], and it has been used in Caucasians [10], Africans [4,11], and Asian [6,12]. To screen objectively diagnostic biomarkers for SHS, several biomarkers, including cortisol [13], relative telomere length [14], intestinal microbiota [15], and metabolites [16], have been investigated. Although previous studies have indicated that multi-omics biomarkers have the potential to diagnose SHS individuals, the underlying mechanisms of SHS remain partially understood.…”
Section: Introductionmentioning
confidence: 99%
“…Suboptimal health status (SHS) has been recognized globally as a health problem among African, Asian and Caucasian populations [2][3][4][5][6][7]. It is a reversible borderline state between health and disease, characterized by declines in vitality, physiological function, and the capacity for adaptation, and does not meet the diagnostic criteria of any medical conditions but reflects the subclinical and reversible stage of a chronic condition, characterized by the perception of health complaints, general weakness and low energy [8].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of SHS is the key to preventing the deterioration of an individual’s health status. SHS can reportedly be measured objectively using the microbiome ( Sun et al, 2020 ), telomere length ( Alzain et al, 2017 ), plasma stress hormones ( Yan et al., 2018 ), plasma metabolites ( Wang et al, 2020 ), glycan ( Adua et al., 2019a ; Adua et al., 2019b ; Wang & Tan, 2019 ), ideal cardiovascular health metrics ( Wang et al, 2017 ), and traditional Chinese medicine ( Wang & Yan, 2012 ; Wang, Russell & Yan, 2014 ). However, these objective measures are not easily accessible, and may sometimes not be obvious, especially when people feel uncomfortable and are without abnormal symptoms.…”
Section: Introductionmentioning
confidence: 99%